Séroprevalencia Toxoplasma gondii u gravidných zien na Slovensku - Studenicová, C; Ondriska, F; Holková, R (Epidemiologie, mikrobiologie, imunologie, 2008)
Toxoplasmosis is caused by a protozoan parasite, Toxoplasma gondii. Primary infection with Toxoplasma gondii in pregnant women can lead to adverse outcomes. Since initially asymptomatic, toxoplasmosis is difficult to diagnose. The aims of this study were to determine the seroprevalence of toxoplasmosis in pregnant women in Slovakia and to identify possible risk factors. As many as 145 (22.1%) of 656 pregnant women screened for T. gondii were seropositive. The prevalence of toxoplasmosis significantly increases with age and the highest seropositivity rate (35.4 %) was found in the age group of 35-44 years. A significantly higher seropositivity rate was observed in women living in the surroundings of Bratislava (63.5%) as compared to Bratislava (36.6%, p < 0.001; OR = 0.53, 95% CI = 0.36-0.79) Among the epidemiological factors, contact with soil appeared statistically significant (35.3%, p = 0.014; OR = 1.67, 95% CI = 1.09-2.56). Fatigue (32.1%, p = 0.026; OR = 1.84, 95% CI = 1.03-3.27), miscarriages (44.1%, p = 0.002; OR = 2.22, 95% CI=1.3-3.8) and toxoplasmosis in the family (10.7%, p = 0.002) were most commonly reported in history of the study subjects.
Keywords: Pregnancy; Humans; toxoplazmóza; parazitární komplikace těhotenství; Female; rizikové faktory; Toxoplasmosis; dospělí; séroepidemiologické studie; lidé; zvířata; Slovakia; Slovenská republika; Adult; ženské pohlaví; Toxoplasma; Seroepidemiologic Studies; Adolescent; těhotenství; Animals; Pregnancy Complications, Parasitic; mladiství; Risk Factors